2019
DOI: 10.1111/jpn.13273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different dietary levels of sodium and chloride on performance and blood parameters in goslings (1–28 days of age)

Abstract: A total of 702 1‐day‐old male Jiangnan White goslings were used to study the effects of varying levels of Na+ and Cl− on their growth performance and blood parameters. In this experiment, goslings were randomly allotted to nine treatments, with six pens per treatment in a 3 × 3 factorial arrangement, and fed diets with three concentrations of added Na+ (0.10%, 0.15% and 0.20%) and three concentrations of added Cl− (0.15%, 0.20% and 0.25%). The purpose of this experiment was to investigate the sensitivity of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In goslings, Buckland and Guy (2002) indicated that at ages of 28–84 days, the dietary requirements for Na + and Cl − were 0.14% and 0.13%, respectively, but for breeder geese during the laying period, the requirements were 0.12% and 0.12%. Based on the results combined with previous laboratory research (Chen et al, 2020), it was found that as age increases, the requirements for Na + and Cl − in poultry gradually decrease. In previous experiments, low levels of Na + and Cl − negatively affected the growth of 1‐ to 28‐day‐old goslings.…”
Section: Discussionmentioning
confidence: 65%
“…In goslings, Buckland and Guy (2002) indicated that at ages of 28–84 days, the dietary requirements for Na + and Cl − were 0.14% and 0.13%, respectively, but for breeder geese during the laying period, the requirements were 0.12% and 0.12%. Based on the results combined with previous laboratory research (Chen et al, 2020), it was found that as age increases, the requirements for Na + and Cl − in poultry gradually decrease. In previous experiments, low levels of Na + and Cl − negatively affected the growth of 1‐ to 28‐day‐old goslings.…”
Section: Discussionmentioning
confidence: 65%
“…The goslings were randomly divided into 5 dietary treatments with 6 replicate pens per treatment and 10 goslings per pen, according to a completely randomized design. The test period lasted for 28 d. Five isonitrogenous and isoenergetic experimental diets were formulated to meet or exceed the nutrient requirements of geese according to the NRC [15] and previous studies on medium-sized geese from our laboratory [16,17]. A corn-soybean meal basal diet (as-fed basis) was used as the control; 25, 50, 75 or 100% of dietary protein provided by SBM was replaced with CSM in the other 4 diet groups (7.08, 14.15, 21.23 and 28.30% CSM, which are referred to as the CSM 25 , CSM 50 , CSM 75 , and CSM 100 groups, respectively).…”
Section: Animals Experimental Design and Managementmentioning
confidence: 99%
“…In both experiments, ve isonitrogenous and isoenergetic diets were formulated to meet or exceed the nutrient requirements of geese according to the National Research Council (NRC) [12] and previous studies on medium-sized geese from our laboratory [13][14][15][16]. A corn-soybean meal (corn-SBM) basal diet was used as the control; 25, 50, 75 or 100% of dietary protein provided by SBM was replaced with protein provided by CSM in the other 4 diet groups (7.08, 14.15, 21.23 and 28.30% CSM (FG: 780 mg/kg) in experiment 1; 5.66, 11.33, 16.99 and 22.65% CSM (800 mg/kg) in experiment 2), which are referred to as the CSM 25 , CSM 50 , CSM 75 , and CSM 100 groups, respectively.…”
Section: Animals Experimental Design and Managementmentioning
confidence: 99%